Challenges for the Large-Scale Integration of Distributed Renewable Energy Resources in the Next Generation Virtual Power Plants - Adrian Gligor; Piotr Cofta; Tomasz Marciniak; Cristian-Dragoș Dumitru (Proceedings, 2020)
The proper power distribution systems operation is conditioned by its response to the consumers’ energy demand. This is achieved by using predictable power sources supplemented by ancillary services. With the penetration of different alternative power sources especially the renewable ones, the grid increasingly becomes an active distribution network. In this context, the stability provided by ancillary services becomes increasingly important. However, providers of ancillary services are interested to benefit from the shift towards renewable energy. This leads to a complex scenario regarding the management of such service providers, specifically virtual power plants. In this regard, the aim of the paper was to investigate the strategies for improving the performance of virtual power plants by increasing the number of distributed renewable energy resources.